Gossypol decreased cell viability and down-regulated the expression of a number of genes in human colon cancer cells - Heping Cao (Nature Portfolio, 2021)
Abstract Plant polyphenol gossypol has anticancer activities. This may increase cottonseed value by using gossypol as a health intervention agent. It is necessary to understand its molecular mechanisms before human consumption. The aim was to uncover the effects of gossypol on cell viability and gene expression in cancer cells. In this study, human colon cancer cells (COLO 225) were treated with gossypol. MTT assay showed significant inhibitory effect under high concentration and longtime treatment. We analyzed the expression of 55 genes at the mRNA level in the cells; many of them are regulated by gossypol or ZFP36/TTP in cancer cells. BCL2 mRNA was the most stable among the 55 mRNAs analyzed in human colon cancer cells. GAPDH and RPL32 mRNAs were not good qPCR references for the colon cancer cells. Gossypol decreased the mRNA levels of DGAT, GLUT, TTP, IL families and a number of previously reported genes. In particular, gossypol suppressed the expression of genes coding for CLAUDIN1, ELK1, FAS, GAPDH, IL2, IL8 and ZFAND5 mRNAs, but enhanced the expression of the gene coding for GLUT3 mRNA. The results showed that gossypol inhibited cell survival with decreased expression of a number of genes in the colon cancer cells.